The Power of a Smile: Exploring the Connection between Teacher Facial Expressions and ESL Learning - Assali, Mouna Abou (Journal of Ecohumanism, 2024)
This research was designed to determine the impact of smiling by an ESL teacher on students' learning achievement. Ten males and six females were interviewed using semi-structured interviews. All of them were students of a higher education program in the United Arab Emirates for the study. The findings suggested that a smile is a major part that can lead to better learning outcomes and affirmed the positive psychology theory. In addition, it was ascertained that a smiling teacher leads to positive changes in attitude; learning climate; motivation and involvement; rapport with the subject; reduction in stress; anxiety; fear and anger; and an improvement in trust and respect. Higher learning outcomes may be achieved through any of these ways. This conceptual model is conducive to empirical research study as presented in this research.